1,1 `-Methylenedipyridinium dichloride monohydrate - Fu, Wen-Zhen; Wang, Wei-Juan; Niu, Yun-Yin; Ng, S.W. (International Union of Crystallography, 2010)
In the crystal structure of the title salt, C(11)H(12)N(2)(2+)center dot 2Cl(-)center dot H(2)O, the dication adopts a butterfly shape [dihedral angle between rings = 69.0 (1)degrees] with the water molecule lying in the V-shaped cavity. Each O-H bond of the water molecule lies parallel to an aromatic ring and forms an O-H center dot center dot center dot Cl interaction to a chloride anion. The methylene C atom in the dication and the water O atoms lie on special positions of twofold site symmetry.